Comparing Dynamic Hyperinflation and Associated Dyspnea Induced by Metronome-Paced Tachypnea Versus Incremental Exercise. (1st February 2014) - Calligaro, Gregory L.; Raine, Richard I.; Bateman, Mary E.; Bateman, Eric D.; Cooper, Christopher B.
Abstract Dynamic hyperinflation (DH) during exercise is associated with both dyspnea and exercise limitation in COPD. Metronome-paced tachypnoea (MPT) is a simple alternative for studying DH. We compared MPT with exercise testing (XT) as methods of provoking DH, and assessed their relationship with dyspnea. We studied 24 patients with moderate COPD (FEV1 59 ± 9% predicted) after inhalation of ipratropium/salbutamol combination or placebo in a double-blind, crossover design. Inspiratory capacity (IC) was measured at baseline and after 30 seconds of MPT with breathing frequencies (fR) of 20, 30 and 40 breaths/min and metronome-defined I:E ratios of 1:1 and 1:2, in random sequence, followed by incremental cycle ergometry with interval determinations of IC. DH was defined as a decline in IC from baseline (∆IC) for both methods. Dyspnea was assessed using a Borg CR-10 scale. ∆IC during MPT was greater with higher fR and I:E ratio of 1:1 versus 1:2, and less when patients were treated with bronchodilator rather than placebo (P = 0.032). DH occurred during 19 (40%) XTs, and during 35 (73%) tests using MPT. Eleven of 18 (61%) non-congruent XTs (where DH occurred on MPT but not XT) terminated before fR of 40 breaths/min was reached. Although greater during XT, the intensity of dyspnea bore no relationship to DH during either MPT and XT. MPT at 40 breaths/min and I:E of 1:1 elicits the greatest ∆IC, and is a more sensitive method for demonstrating DH. The relationship between DH and dyspnea is complex and not determined by DH alone.